THE INVOLVEMENT OF EX-TERRORIST INMATES AND COMBATANTS IN THE DISENGAGEMENT FROM VIOLENCE STRATEGY IN INDONESIA - Widya, Bella; Syauqillah, Muhamad; Yunanto, Sri (Journal of Terrorism Studies, 2020)
In Indonesia, there are a number of foundations which were established by the ex-terrorist inmates as a new community towards peace and a way of empowerment for the ex-terrorist inmates. The involvement of ex-terrorist inmates in disengagement strategy in Indonesia has also raised pro(s) and con(s). This research aims to explore the involvement of ex-terrorist inmates in disengagement strategy in Indonesia. This kind of involvement is hoped to become a softer approach because it focuses more in using kinship method, in a way that it will be easier to gain trust, and the people have the same experience and background in terrorism. The methodology used in this research is a qualitative with interview technique. This research found that the phenomenon of the arousal of new communities towards peace which was established by ex-terrorist inmates and combatants is a positive thing as a new medium for those inmates and other inmates who has the desire to come and disengage from violence. However, this kind of phenomenon has to be guided, guarded and controlled by the government in order to keep it in line with the true purpose of deradicalization and counter strategy of terrorism in Indonesia.